(untitled) (Revista de Estudos da Linguagem, 2024)
This article intends to systematize a discussion on the ways in which transformations imbricated in the passage from Fordism-Taylorism to post-Fordism are associated with the development of interaction processes and linguistic practices in which traits such as technologization, virtualization, and de-referentialization are presented as constitutive elements. The argumentation mobilizes theoretical and analytical contributions that focus on the forms of organization assumed by post-industrial capitalism, including those of Harvey (2010) and Castells (2002), with which it seeks to articulate approaches focused on the role of language in the configuration of post-Fordist society, in particular those of Lazzarato (2014), Berardi (2020) and Virno (2014). The corpus of the article consists of excerpts from utterances collected in interaction processes observed on various online platforms and applications. Among the conclusions to which the argumentation developed in the article leads can be indicated the idea that the prominence of information and communication technologies brought about by the post-Fordist system of production and social regulation has as one of its effects the constitution of a technolanguage that, inscribed in different linguistic-discursive practices, is characterized, among other things, by the hybridization of real and virtual, natural and artificial, human and machinic elements.